2009
DOI: 10.1186/1471-2458-9-182
|View full text |Cite
|
Sign up to set email alerts
|

Effective elements of school health promotion across behavioral domains: a systematic review of reviews

Abstract: Background: Most school health education programs focus on a single behavioral domain. Integrative programs that address multiple behaviors may be more efficient, but only if the elements of change are similar for these behaviors. The objective of this study was to examine which effective elements of school health education are similar across three particular behavioral domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0
15

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(170 citation statements)
references
References 68 publications
6
144
0
15
Order By: Relevance
“…Thus, the implementation of health education or intervention programmes in the school setting is an important component of disease prevention. However, Peters et al, (2009), underscored that behavioural change does not necessarily flow from improved knowledge about risk factors for CDL, as is evident in the increased health risk behaviours among youth (Reddy et al, 2010). In the South African setting, the Youth Risk Behaviour Survey (YRBS) was conducted in 2002 and 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the implementation of health education or intervention programmes in the school setting is an important component of disease prevention. However, Peters et al, (2009), underscored that behavioural change does not necessarily flow from improved knowledge about risk factors for CDL, as is evident in the increased health risk behaviours among youth (Reddy et al, 2010). In the South African setting, the Youth Risk Behaviour Survey (YRBS) was conducted in 2002 and 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that there is an implementation problem among teachers but teachers themselves do not perceive this sub-optimal implementation behavior as a problem (Bessems et al, 2014;Peters et al, 2009;Dusenbury et al, 2003;Dusenbury, Brannigan, Hansen, Walsh, & Falco, 2005;Martens, Van Assema, Paulussen, Schaalma, & Brug, 2006). In the case of LLL, teachers did not deliver lessons completely and according to the goals of program designers but teachers did not perceive this behavior as problematic or as a necessity to effectively provide the lessons.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of these programs on the health of the youth is, besides the quality of the program itself, also dependent on the quality of implementation. The reach and implementation of school-based health promotion programs is, however, not optimal (Bessems, van Assema, de Vries, & Paulussen, 2014;Peters, Kok, Ten Dam, Buijs, & Paulussen, 2009;Schutte et al, 2014;Forman et al, 2009). Figure 1 shows the implementation process of school-based programs when program developers do not intervene in the process; only 70% of the target population is aware of the program, 50% decide to use it (adoption), 30% actually use it (implementation), and a small 10% continues to use the program in the long-run (continuation) (Paulussen, Kok, Schaalma, & Parcel, 1995;Paulussen, Kok, & Schaalma, 1994).…”
Section: Implementation Of School-based Sexual Health Education Programsmentioning
confidence: 99%
See 2 more Smart Citations